Preparation and characterization of cefuroxime axetil solid dispersions using hydrophilic carriers - Gorajana, Adinarayana; Rajendran, Adhiyaman; Yew, Lee Mun; Dua, Kamal (International Journal of Pharmaceutical Investigation)
Aim: The objective of the current study is to increase the dissolution rate of cefuroxime axetil (CA) by formation of binary CA solid dispersion using water soluble carriers such as polyvinylpyrrolidone (PVP K30) and polyethylene glycol (PEG 4000). Methods: Solid dispersions (SDs) between CA and PVP K30/PEG 4000 were formed by dissolving both compounds in a common solvent, methanol, which were rotary evaporated at 40°C for 12 h. Physical mixtures between CA and PVP K30/PEG 4000 were also formulated as to compare the effi ciency of SDs. The physicochemical properties of CA and all its formulations were then characterized using differential scanning calorimetric analysis (DSC), powder X-ray diffraction studies (PXRD), and Fourier transform infrared spectroscopy (FTIR). Results: All SD formulations were found to have a higher dissolution rate comparatively to pure CA, while only physical mixtures of PVP K30 were found having a signifi cantly higher dissolution rate. The enhancement of dissolution rate SD by PVP K30 may be caused by increase wettability, solubility, reduction in particle size or the formation of CA β crystalline. Increment of dissolution rate of CA SDs by PEG 4000 similarly may be caused by increase wettability, solubility, and reduction in particle size. This phenomenon may also be caused by amorphization as suggested by DSC and PXRD. Conclusions: The SD of CA with PVP K30 and PEG 4000, lends an ample credence for better therapeutic effi cacy.
Keywords: Cefuroxime axetil; dissolution; polyethylene glycol 4000; polyvinylpyrrolidone K30; solubility